PENERAPAN ALGORITMA DIJKSTRA DALAM PENENTUAN LINTASAN TERPENDEK MENUJU UPT. PUSKESMAS CILODONG KOTA DEPOK - Cicih Sri Rahayu; Windu Gata; Sri Rahayu; Agus Salim; Arif Budiarto (JURNAL TEKNIK INFORMATIKA, 2021)
One of the government's efforts in providing health to the community is the construction of health centers in each sub-district, and the community is expected to be able to take advantage of the health facilities provided by the government. One of the problems that exist in the community is determining the shortest distance to the puskesmas. In Depok City, there are 26 routes that can be passed from the 38 nodes or vertices to the Cilodong Health Center with the starting point of the Depok mayor's office. This study uses a survey research method to calculate the actual distance at each node or vertex, the purpose of this study is to determine the shortest path taken by the starting point from the Depok mayor's office to get to the Cilodong Health Center by applying the dijkstra algorithm. This dijkstra algorithm works by visiting all existing points and making a route if there are 2 routes to the same 1 point then the route that has the lowest weight is chosen so that all points have an optimal route. This quest continues until the final destination point. After doing this research and testing using a simple application to calculate the distance by applying the djikstra algorithm, it was found that the shortest path taken to the destination is through the GDC Main Gate or on the test results in Iteration 26. From the results of this study, people can choose this closest route to save time when viewed from the distance of the existing track. For further research, it is expected to be able to compare two other algorithms and other parameters so that the closest route with the fastest time is obtained.